Effects of pH, titratable acidity and calcium concentration of non alcoholic carbonated beverages on enamel erosion: an in vitro study. (Nigerian Dental Journal, 2010)
Objective: Beverage acidity has been measured routinely using the pH value. However, titratable acidity is thought to be a true indicator of beverage erosive potential. It has also been reported that experimental addition of calcium in beverages can reduce the progression of erosion. This study was carried out to investigate effects the of pH, titratable acidity and calcium concentration of non alcoholic carbonated beverages on enamel erosion of extracted human premolar teeth.Method: The erosive potential of 13 carbonated beverages and control was characterized based on analysis of pH, titratable acidity, and calcium concentrations. This was followed by ename demineralization tests. Baseline and post-immersion measurements of enamel microhardness were carried out using Vickers microhardness tester. Mean and standard deviation for each parameter was calculated. One way analysis of variance (ANOVA), paired t test, pearson's correlation, and multiple linear stepwise regression analysis were employed for statistical analysis. P values
Keywords: Tooth wear; Enamel erosion; Beverages; Enamel microhardness